SPE/DOE Improved Oil Recovery Symposium 2002
DOI: 10.2118/75228-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Crude Oils by SARA Analysis

Abstract: The effectiveness of some improved oil recovery schemes can depend on the composition of the target oil. Crude oils can be described compositionally by a number of methods. SARA analysis divides crude oil components according to their polarizability and polarity using a family of related analytical techniques. Problems arise because several of the analytical techniques in use do not produce identical results, although the users of the data rarely distinguish between them, assuming that SARA fraction values gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 14 publications
0
75
0
1
Order By: Relevance
“…Leontaritis and Mansoori [17] recommended using the ratio of resins to asphaltenes as an indicator of asphaltene stability, based on the hypothesis that resins confer asphaltene stability by peptizing (or coating) asphaltenes. Fan et al [27] observed that the proportions of each of the SARA fractions in a crude oil are related to the stability of asphaltenes in that oil. Alkafeef et al [28] define the stability of a colloid dispersion as its resistance to flocculation, and the degree of "resistance" is used as a measure of the dispersion stability.…”
Section: Screening Technique For Asphaltene Stabilitymentioning
confidence: 99%
“…Leontaritis and Mansoori [17] recommended using the ratio of resins to asphaltenes as an indicator of asphaltene stability, based on the hypothesis that resins confer asphaltene stability by peptizing (or coating) asphaltenes. Fan et al [27] observed that the proportions of each of the SARA fractions in a crude oil are related to the stability of asphaltenes in that oil. Alkafeef et al [28] define the stability of a colloid dispersion as its resistance to flocculation, and the degree of "resistance" is used as a measure of the dispersion stability.…”
Section: Screening Technique For Asphaltene Stabilitymentioning
confidence: 99%
“…Taylor et al demonstrated that the onset of asphaltene precipitation could be detected from RI measurement (Taylor et al 2001). Fan et al (2002) examined the relation between crude oil RI and asphaltene stability in crude oil. They suggested that the difference between crude oil RI and crude oil RI at the onset of asphaltene precipitation could be employed as a decisive factor for the assessment of asphaltene stability in crude oils (Fan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al (2002) examined the relation between crude oil RI and asphaltene stability in crude oil. They suggested that the difference between crude oil RI and crude oil RI at the onset of asphaltene precipitation could be employed as a decisive factor for the assessment of asphaltene stability in crude oils (Fan et al 2002). Buckley and Wang (2002) showed that the wettability altering tendency is related to crude oil RI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations